Domestic science club demonstration - Pierce, Marcia (My University, 1908)
Introduction: Food has been described as those substances which taken into the body may be used to build tissue, repair waste and furnish any form of energy. In preparing foods in this short course of Domestic Science, it shall be the object to prepare them in the best possible way. The senses of taste and sight should always be appealed to.
Citation: Pierce, Marcia. Domestic science club demonstration. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Food; Recipes; Graduating theses; Senior theses; Theses